1964
DOI: 10.1002/aic.690100133
|View full text |Cite
|
Sign up to set email alerts
|

Scale of mixing in a stirred vessel

Abstract: Although stirred vessels are widely used in chemical technology, they have been characterized almost exclusively by empirical methods, for example power absorption per unit volume (11) The present work investigates simultaneous mixing and reaction of a basic tracer stream with a surrounding acid medium. A steady state condition is achieved by continuously introducing a tracer sodium hydroxide solution into an acid stream which flows slowly upward through the stirred vessel. Both base and acid streams contain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0

Year Published

1965
1965
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 7 publications
5
7
0
Order By: Relevance
“…These results illustrate strong flow compartmentalizations which also have been reported in previous experimental and numerical studies for Newtonian laminar flow fields in a stirred tank equipped with a RT 21–23 and also for a sawtooth HSI in the turbulent flow regime 12. Rice et al 23 stated that for Re < 500 the flow induced by many flat‐blade turbines divides the tank in two regions of two ring vortices. It was found that there is a greater intensity (about 6 %) of the axial flow in the upper loop in both HSIs with respect to the lower loop, and in general this behavior is similar for the RT.…”
Section: Resultssupporting
confidence: 83%
“…These results illustrate strong flow compartmentalizations which also have been reported in previous experimental and numerical studies for Newtonian laminar flow fields in a stirred tank equipped with a RT 21–23 and also for a sawtooth HSI in the turbulent flow regime 12. Rice et al 23 stated that for Re < 500 the flow induced by many flat‐blade turbines divides the tank in two regions of two ring vortices. It was found that there is a greater intensity (about 6 %) of the axial flow in the upper loop in both HSIs with respect to the lower loop, and in general this behavior is similar for the RT.…”
Section: Resultssupporting
confidence: 83%
“…These investigations were oriented towards the evaluation of the power curves of different impeller configurations under various operating conditions. Furthermore, methods for estimating mixing times have been set up from the experimental analysis of tracer dispersion (Metzner and Taylor, 1960;Biggs, 1963;Rice et al, 1964).…”
mentioning
confidence: 99%
“…The scale expression, Equation (6), when applied to the test conditions of Rice et a1 (11) predicts length scale values which are larger by a factor of about 30 than estimated by their experiments. However, it may be noted that scale values of the same order of magnitude as those of Rice can be obtained by Equation (6) if the volume swept out by the impeller is used as the volume term in Equation (7).…”
Section: The Length Scale (I) Expressionmentioning
confidence: 82%
“…This is because of the large amount of information required for such a description: n ( n -1)/2 diffusivities and associated activity data for a system of n diffusing species.' The most complete available treatments appear to be those of Spiegler (13) and Mackay and Meares (11).…”
Section: 62mentioning
confidence: 99%